Literasi Wajib Pajak Tentang Tarif Efektif Rata-rata pada Pemungutan PPh Pasal 21 - Rizky Putri Lisdiana; R. Muh. Syah Arief Atmaja Wijaya (Economic Reviews Journal, 2024)
Income Tax 21 with an average effective rate scheme is the average tax rate actually paid by taxpayers after taking into account applicable deductions and deductions. This study aims to analyze taxpayer knowledge about Income Tax Article 21 with an average effective rate scheme. This type of research is a descriptive research with a qualitative approach. Data collection was carried out through interviews and observations. The results of this study show that the public's understanding of Income Tax 21 effective tariff scheme on average is low. This is caused by uneven dissemination of information or socialization from the government and tax officials.